Accessibility and dissemination of the cultural heritage in a museum library: case study in the National Archaeological Museum (Spain) - Cobo-Serrano, Silvia; Arquero-Avilés, Rosario; Marco-Cuenca, Gonzalo (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2023)
The bibliographic heritage held by GLAM (Galleries, Libraries, Archives and Museums) institutions is an invaluable source for research, culture and education in a country. This paper aims to present a research project plan to improve the visibility, accessibility and dissemination of the bibliographic heritage of the National Archaeological Museum Library through the generation of virtual bibliographic exhibitions. The research project is highly praiseworthy and innovative in the field of Spanish heritage. Firstly, this is the first challenge undertaken in a Spanish state museum library with the stated general objective and, secondly, because the project proposal was supported and funded in 2021 by the Spanish Ministry of Science and Innovation in the call ‘R+D+i Oriented to the Challenges of Society’. After formulating some research questions, the research design was divided into five phases. It included drafting scientific-technical reports, selecting stakeholders as well as the configuration of the project team to conclude with the project implementation phase. The proposed research project plan also included the general and specific objectives, the research team, phases of the proposal as well as its dissemination and communication plan. Conclusions highlight the importance of creating multidisciplinary work teams and combining the use of technologies with the bibliographic collections of cultural institutions.